The Relationship between D-Dimer Levels and Coronary Lesion Severity in Patients with Acute Myocardial Infarction with ST-Segment Elevation at Haji Adam Malik Hospital Medan - Rialdy, M. Isfan; Akbar, Nizam Zikri; Haykal, T. Bob; Ketaren, Andre Pasha; Andra, Cut Aryfa; Sarastri, Yuke (CoinReads Media Prima, 2023)
Introduction: Acute coronary syndrome results from rupture or erosion of an atherosclerotic plaque. D-dimer is a direct marker of fibronolysis events and an indirect marker of hypercoagulable state associated with atherosclerotic plaque formation and acute coronary syndrome. The purpose of this study was to determine the relationship between D-dimer levels and the severity of coronary lesions in ST Elevation Myocardial Infarction patients at H. Adam Malik Hospital Medan. Method: This study was conducted with a cross-sectional method on 72 ST Elevation Myocardial Infarction patients at H. Adam Malik Medan Hospital who underwent coronary angiography from December 2022 to May 2023. Definition of ST Elevation Myocardial Infarction followed the definition of Universal Definition of Myocardial Infarction and the severity of coronary lesions was calculated based on syntax score. Data were analyzed univariately and bivariately using SPSS to assess the association of D-dimer levels with syntax score with p<0.05 considered statistically significant. Results: The total study subjects were 72 people with an average age of 56,5410,84years. Most of the study samples were male 56 people (77.8%). The median D-dimer level was 605 and mean syntax score 22.027 + 14.61. There is a significant relationship between D-dimer levels and the severity of coronary lesions based on the syntax score (p: <0.001). Conclusion: There is a significant relationship between D-dimer and severity of coronary lesions in patients with acute myocardial infarction with ST segment elevation at H. Adam Malik General Hospital, Medan.